PEMETAAN PERSEBARAN MAHASISWA JURUSAN TEKNIK INFORMATIKA ANGKATAN TAHUN 2020 POLITEKNIK NEGERI BATAM BERDASARKAN ASAL SEKOLAH MENGGUNAKAN WEBGIS - Putri Nadia; Farouki Dinda Rassarandi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The need for easy information is a major need for the global community, not only in Indonesia, especially for student groups, students, educational institutions, government, and so on. This need is the need for information in the form of geographical content. Geographic information systems are work systems for collecting, managing, manipulating, analyzing, and interpreting other information. The first step taken to build WebGIS is to collect data in the form of school information and school name data, then take field data using GPS Handheld tools, to retrieve school points, and will continue data processing as well as reusability testing and system testing. The results of WebGIS usability testing using the SUS method are 75 grade scale B, and adjective ratings are include in the Good category, where WebGIS has an average value and can be said to be suitable for general use